Kelola Pangen Sehat Bergizi untuk Tumbuh Kembang Anak dan Atasi Stunting di Kelurahan Kedungpane, Mijen, Kota Semarang - Hermanu, Bambang; Nurlaili, Enny Purwati; Kartikawati, Diah; Ilminingtyas W.H, Dyah; Umar Dhani, Ali; Ayu Artiningsih, Ni Komang; Nurtekto; Hartoyo, Budi (Perigel: Jurnal Penyuluhan Masyarakat Indonesia, 2024)
Stunting is a chronic malnutrition problem that has a serious impact on child growth and development. This article examines the role of families in providing healthy and nutritious food to prevent stunting in infants. Through literature reviews, case studies, and real-world conditions, it was found that the availability of nutritious food in households, good feeding practices, and mothers' knowledge of nutrition significantly influence children's nutritional status. This article suggests the importance of integrated interventions, including nutrition education for mothers, the provision of nutritious complementary foods, and social support for families, to increase the consumption of nutritious foods in infants and prevent stunting.